2018
DOI: 10.1007/s10661-018-6655-x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of thiamethoxam residues in banana stem and fruit through LC-MS/MS

Abstract: An analytical method based on liquid chromatography coupled with mass spectroscopy/mass spectroscopy was developed and validated for the determination of thiamethoxam residues in banana fruit and stem tissue samples. In this study, Waters Alliance LC and Acquity TQD were used with an electrospray ionization interface in the positive ion mode. An isocratic flow of 0.5% HCOOH in water and 0.05% HCOOH in CHCN was used for separation. Thiamethoxam residue was extracted from the samples using CHCN and a dispersive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…1), is a nitro-neonicotinoid insecticide which interferes with the nicotinic acetylcholine receptor and thus affects the insect nervous system 19 . Several methods were reported for determination of TMX by liquid and gas chromatography alone in honeybees, fruits and vegetables 20,21 or with other neonicotinoids [22][23][24][25] . Studies showed that TMX disturbs hepatic and renal functions, provokes an increase in glucose levels and undesirable neurological effects in rats 26 .…”
Section: Thiamethoxammentioning
confidence: 99%
“…1), is a nitro-neonicotinoid insecticide which interferes with the nicotinic acetylcholine receptor and thus affects the insect nervous system 19 . Several methods were reported for determination of TMX by liquid and gas chromatography alone in honeybees, fruits and vegetables 20,21 or with other neonicotinoids [22][23][24][25] . Studies showed that TMX disturbs hepatic and renal functions, provokes an increase in glucose levels and undesirable neurological effects in rats 26 .…”
Section: Thiamethoxammentioning
confidence: 99%
“…However, there are a few constraints on the adoption of CSA technologies, some of which are a lack of knowledge, insufficient finance opportunities, and a lack of policies to push its implementation. There is a need for different practices which may be suitable for different kinds of soil, and climatic conditions which are also economically viable [16]. For India, which has so much diversity when it comes to soil types and climatic conditions, not one model of development can be suitable for all regions.…”
Section: Introductionmentioning
confidence: 99%
“…Clothianidin, a metabolite of thiamethoxam, is also another neonicotinoid insecticide 5,6 . In the previous literature, a number of studies on the residual behavior of thiamethoxam in rice grain, 7 mango, 8 banana, 9 strawberry, 10 pomegranate, 11 apple, 12 cowpea 13 and citrus 14 have been reported domestically and internationally. However, there was no systematic study conducted on degradation behavior, residue distribution and dietary risk assessment of thiamethoxam in Chinese kale.…”
Section: Introductionmentioning
confidence: 99%
“…Thiamethoxam and clothianidin residues were usually extracted from different vegetables matrices using acetonitrile. The commonly used analytical instruments for thiamethoxam analysis are gas chromatography (GC), 15 liquid chromatography (LC) 16,17 and LC‐tandem mass spectrometry (LC–MS/MS) 9‐11,13,14,18 . In addition, we can see the modified quick, easy, cheap, effective, rugged, and safe (QuEChERS) sample preparation procedures have been successfully used to recover thiamethoxam and clothianidin from banana, 9 citrus, 14 cowpeas 13 and strawberries 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation